Uremic stomatitis in patients with chronic renal failure undergoing hemodialysis: Stomatitis uremia pada penderita penyakit gagal ginjal kronis yang menjalani hemodialisis - Alamsyah Piliang; Nelly Nainggolan; Riani Setiadhi (Makassar Dental Journal, 2022)
Patients with end-stage renal disease with or without hemodialysis are at risk of experiencing a number of comorbidities inclu-ding hypertension, anemia, risk ofbleeding and have oral manifestations related to the disease itself or due to hemodialysis; for example uremic stomatitis. This article describes uremic stomatitis in end-stage renal disease patient undergoing hemodialysis. A 14-year-old girl with chronic kidney disease had already undergoing hemodialysis, came with weak, pale condition and pre-viously vomiting, complaining sore mouth and difficult to eat. Extra oral revealed anemic conjunctiva, dry lips, exfoliative, ero-sive with serosanguinolenta crusts, tend to bleed, multiple purpuras and petechiae on the lower lip. Intra oral showed white plaque cannot be scrapped off on theventral tongue. Painful erosive area and white pseudomembranes on the lower labial mu-cosa, multiple white plaques can be scrapped off leaving erythematous area on the right buccal mucosa, purpura on the left buc-cal mucosa. Laboratory examination supported the diagnosis as as uremic stomatitis and exfoliative cheilitis. To overcome the complaints and improve the oral condition, the patient was treated with 0.12% chlorhexidine digluconate 0.12%, 0.9% NaCl solution, a mixture of tranexamic acid vials and aqua bides, and vaseline album. It was concluded that uremic stomatitis is an oral manifestation of end-stage renal disease, and appropriate therapy will improve the quality of life of the patient.